(untitled) (Baghdad Science Journal, 2025)
Thin films of pure tin mono-sulfide SnS and tin mono-sulfide for (1,2,3,4)% fluorine SnS:F with Thicknesses of (0.85 ±0.05) ?m and (0.45±0.05) ?m respectively were prepared by chemical spray pyrolysis technique. the effect of doping of F on structural and optical properties has been studied. X-Ray diffraction analysis showed that the prepared films were polycrystalline with orthorhombic structure. It was found that doping increased the intensity of diffraction peaks. Optical properties of all samples were studied by recording the absorption and transmission spectrum in range of wave lengths (300-900) nm. The optical energy gap for direct forbidden transition and indirect allowed transition were evaluated It is found that for doping less than 2% the optical energy gap increases as the percentage of doping increases in the samples while for doping more than 2% the values of the optical energy gap decreases as the percentage of doping increases.